STUDI ETNOBIOLOGI PANDANUS DI PAPUA - Maria Justina Sadsoeitoeboen; Agustinus Kilmaskossu (FMIPA Universitas Papua, 2007)
A research was carried out to study the diversity of Pandanus in the Papua region. The aim of the study was to find out how many species of Pandanus were all ready known by the people and used in their daily life. There are 42 species of Pandanus found in Papua. Based on the traditional utilization of the people in the Papua Tribe, Pandanus can be divided into seven group, i.e.: (1) species which are used for edible fruit, (2) species which are used for floor of houses, (3) species which are used for roofing, (4) species which are used for sleeping mat and rain covering, (5) species used for hunting, (6) species used for medicine, and (7) species which are still unknown.